Diurnal distribution of carbohydrates and fat affects substrate oxidation and adipokine secretion in humans. Issue 6 (12th December 2018) - Kessler, Katharina; Hornemann, Silke; Petzke, Klaus J; Kemper, Margrit; Markova, Mariya; Rudovich, Natalia; Grune, Tilman; Kramer, Achim; Pfeiffer, Andreas F H; Pivovarova-Ramich, Olga
ABSTRACT: Background: A diet in which fat is mainly eaten in the morning and carbohydrates mainly in the evening (compared with the reverse order) was recently shown to worsen glycemic control in people with prediabetes. Objective: We investigated the effects of these dietary patterns on energy metabolism, and on the daily profiles of circulating lipids, adipokines, and inflammatory markers. Design: In a randomized controlled crossover trial, 29 nonobese men (with normal glucose tolerance, n = 18; or impaired fasting glucose/glucose tolerance, n = 11) underwent 2 isocaloric 4-wk diets: 1 ) carbohydrate-rich meals until 1330 and fat-rich meals between 1630 and 2200 (HC/HF); or 2 ) the inverse sequence of meals (HF/HC). During a 12-h clinical investigation day after each intervention period, 2 meal tolerance tests were performed, at 0900 and 1540, respectively. Substrate oxidation and concentrations of circulating lipids, adipokines, and cytokines were assessed pre- and postprandially. The postprandial inflammatory response in leukocytes was analyzed ex vivo. Results: Fasting carbohydrate oxidation decreased ( P = 0.004) and lipid oxidation increased ( P = 0.012) after the HC/HF diet. Fasting concentrations of blood markers did not differ between diets. The diets modulated the daily profiles of carbohydrate oxidation, lipid oxidation, and β-hydroxybutyrate, although the average daily values of these parameters showed no difference between the diets, and no interaction between diet and glucose tolerance status. Diurnal patterns of triglycerides, low-density lipoprotein cholesterol, leptin, visfatin, and of LPS-induced cytokine secretion in blood leukocytes were also modulated by the diets. Average daily concentrations of leptin ( P = 0.017) and visfatin ( P = 0.041) were lower on the HF/HC diet than on the HC/HF diet. Conclusions: Diurnal distribution of carbohydrates and fat affects the daily profiles of substrate oxidation, circulating lipids, and cytokine secretion, and alters the average daily concentrations of adipokine secretion in nonobese nondiabetic humans. The study was registered at clinicaltrials.gov as NCT02487576.